POLA TANAM DAN KETERSEDIAAN SUMBER DAYA PANGAN DI KAWASAN HUTAN MURIA (KHM) - Banowati, Eva (Faculty of Social Science, Universitas Negeri Semarang, 2010)
Forest production in Muria in Forest Area (KHM) potential as food resources. The purpose of the studyexamines: (1) planting pattern of the practise, and (2) the extent to which cultivated crops contribute tofood availability. Pesanggem population in three villages in the KHM of 632 people, 345 people respondentsample is determined randomly. Spatial analysis used to assess the distribution of plants, descriptionspercentage to obtain borgan use structure that contribute to food availability. Signifi cance of the resultssupported the analysis of fi eld observations, interviews, FGDs, in-depth interviews (depth-interview).The results of this study were: (1) mixed cropping economical and ecologically-oriented, and (2) peanutcrops contribute to food availability this is related to the selling price reaches Rp.1.300.000, 00 in theharvest area 0.25 ha. Based on a depth-interview note that pesanggem desperately need borgan as a foodcrop farms. In addition, these plants because they prioritize the experience they know that peanuts havethe nature of fertile land.Key Words: Borgan, pesanggem, cropping pattern.